2022
DOI: 10.3390/s22103765
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of Articular Cartilage Damage Based on Generated Acoustic Signals Using ANN—Part II: Patellofemoral Joint

Abstract: Cartilage loss due to osteoarthritis (OA) in the patellofemoral joint provokes pain, stiffness, and restriction of joint motion, which strongly reduces quality of life. Early diagnosis is essential for prolonging painless joint function. Vibroarthrography (VAG) has been proposed in the literature as a safe, noninvasive, and reproducible tool for cartilage evaluation. Until now, however, there have been no strict protocols for VAG acquisition especially in regard to differences between the patellofemoral and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 125 publications
(145 reference statements)
0
19
0
Order By: Relevance
“…Identifier 7 is Kurtosis, which is a measure of the spread of a data distribution, calculated using Equation (5) [ 32 ]. where is the fourth moment and is the standard deviation.…”
Section: Methodsmentioning
confidence: 99%
“…Identifier 7 is Kurtosis, which is a measure of the spread of a data distribution, calculated using Equation (5) [ 32 ]. where is the fourth moment and is the standard deviation.…”
Section: Methodsmentioning
confidence: 99%
“…The use of artificial intelligence in medicine has been gaining recognition in the medical community, e.g. in radiology [30,31] and diagnosis of selected disease entities [32][33][34][35][36][37]. It allows for rapid and precise analysis of many parameters which can potentially be used in predicting the outcomes of injuries.…”
Section: Introductionmentioning
confidence: 99%
“…The use of numerical, statistical, and machine-learning methods can complement typical experimental studies and may allow a better understanding of the complex relationships commonly found in medicine [20][21][22][23]. Statistical analyses based on the ICD-10 classification are particularly useful in trauma research because they allow the classification and comparison of different types of injuries and their prevalence in the population [24].…”
Section: Introductionmentioning
confidence: 99%